Anaerobic ciliates as a model group for studying symbioses in oxygen‐depleted environments. (3rd May 2022) - Rotterová, Johana; Edgcomb, Virginia P.; Čepička, Ivan; Beinart, Roxanne
Abstract: Anaerobiosis has independently evolved in multiple lineages of ciliates, allowing them to colonize a variety of anoxic and oxygen‐depleted habitats. Anaerobic ciliates commonly form symbiotic relationships with various prokaryotes, including methanogenic archaea and members of several bacterial groups. The hypothesized functions of these ecto‐ and endosymbionts include the symbiont utilizing the ciliate's fermentative end products to increase the host's anaerobic metabolic efficiency, or the symbiont directly providing the host with energy by denitrification or photosynthesis. The host, in turn, may protect the symbiont from competition, the environment, and predation. Despite rapid advances in sampling, molecular, and microscopy methods, as well as the associated broadening of the known diversity of anaerobic ciliates, many aspects of these ciliate symbioses, including host specificity and coevolution, remain largely unexplored. Nevertheless, with the number of comparative genomic and transcriptomic analyses targeting anaerobic ciliates and their symbionts on the rise, insights into the nature of these symbioses and the evolution of the ciliate transition to obligate anaerobiosis continue to deepen. This review summarizes the current body of knowledge regarding the complex nature of symbioses in anaerobic ciliates, the diversity of these symbionts, their role in the evolution of ciliate anaerobiosis and their significance in ecosystem‐level processes.